Structure - Activity relations for the photodegradation reactions of monosubstituted anilines in TiO2 suspensions - San, N; Çinar, Z (WALTER DE GRUYTER GMBH, 2002)
The kinetics of the photocatalytic degradation reactions of nine different monosubstituted anilines have been investigated experimentally and theoretically. With the intention of finding certain indices in order to determine the degradation rates of aromatic pollutants, geometry optimizations of the anilines have been performed with the semi-empirical PM3 method. The molecular orbital calculations have been carried out by a self-consistent field SCF method using the restricted Hartree-Fock RHF formalism. The correlations between the apparent first-order rate constants and the molecular properties of the compounds have been examined. Three different quantitative structure-activity relationships, QSARs were developed expressing the logarithms of the rate constants in terms of the Brown constants sigma(+) and electron densities of the substituents q, 1-octanol/water partition coefficients log K-OW and the energies of the highest occupied molecular orbitals E-HOMO.
Keywords: photocatalytic degradation; titanium dioxide; anilines; QSAR; quantum mechanical indices; ILLUMINATED TITANIUM-DIOXIDE; PHOTOCATALYTIC OXIDATION; WASTE-WATER; AQUEOUS SUSPENSIONS; PHENOL; BIODEGRADATION; CHROMATOGRAPHY; DEGRADATION; GAS; Chemistry